Consumers' preferences on the Swiss car market: A revealed preference approach - Sylvain Weber (University of Neuchâtel, Institute of Economic Research (IRENE), 2018)
This paper investigates demand responses to variations in the characteristics of the vehicles. Our investigation is based on number of sales for each model marketed over the period 2006-2015 in Switzerland, and puts particular emphasis on fuel efficiency, curb weight, horsepower, and the potential interactions between these attributes. We find that market shares are significantly higher for more efficient and powerful vehicles, while light cars are preferred to heavy ones. Our results also point to a gradual increase of sensitivity to fuel efficiency over the last decade. However, interaction effects between engine fuel efficiency and power indicate a lower marginal valuation of fuel efficiency in the market segments for relatively powerful cars, hence a lower sensitivity to fuel efficiency among the consumers with the highest potential for polluting emissions. Also, these findings point to potential rebound effects, where consumers give up part of the expected fuel savings by purchasing more powerful vehicles.
Keywords: D12; Q41; R41; 330; willingness-to-pay; engine fuel efficiency; car weight; horsepower; rebound effect